2017
DOI: 10.3168/jds.2017-12637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary flax seed and oil on milk yield, gross composition, and fatty acid profile in dairy cows: A meta-analysis and meta-regression

Abstract: Several experiments were conducted over the past few years to evaluate the feeding value of flax seed and oil in dairy cow diets. The current meta-analysis and meta-regression was undertaken to assess the overall effect of different forms of flax, as a source of trienoic (cis-9,cis-12,cis-15 18:3) fatty acids (FA), on lactation performance and on transfer efficiency of its constituent n-3 FA from diet to milk fat. Comparisons were first conducted with nonsupplemented controls or with diets containing either sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 121 publications
1
35
2
Order By: Relevance
“…In particular, the EFA treatment did not reduce DMI, even at the highest dosage administered in this study. In contrast, previous studies indicated a DMI depression with linseed, either administered via feed and passing the rumen or infused into the abomasum (Leduc et al, 2017;Moallem, 2018). The hypophagic effect known for PUFA probably did not occur in the current study because of the relatively low dosages of linseed oil applied.…”
Section: Effects Of Fa Supplementation On Performance and Milk Productioncontrasting
confidence: 84%
“…In particular, the EFA treatment did not reduce DMI, even at the highest dosage administered in this study. In contrast, previous studies indicated a DMI depression with linseed, either administered via feed and passing the rumen or infused into the abomasum (Leduc et al, 2017;Moallem, 2018). The hypophagic effect known for PUFA probably did not occur in the current study because of the relatively low dosages of linseed oil applied.…”
Section: Effects Of Fa Supplementation On Performance and Milk Productioncontrasting
confidence: 84%
“…Also, the later authors cleared that increasing milk harvest which shown with sunflower oil may be due to the great of total volatile fatty acids (tVFA) concentration in rumen of goats fed diets added with sunflower oil, and consequent increased value of Nutilization efficiency, as well as an increased conversion and availability of nutrients for milk synthesis. Recently, these results are corresponding with the findings of other studies by Khalifa et al (2016) and Leduc et al (2017). They found more milk production with diet contained oils that may be due to efficient anaerobic fermentation, which increase organic matter and fibers digestibility and then improve milk yield.…”
Section: Milk Harvestsupporting
confidence: 88%
“…Considerable evidence exists that milk fatty acid composition can be modulated by adding oilseeds to the diet of dairy cows (Chilliard et al, 2007). In addition to being effective in limiting CH 4 production by dairy cows, several meta-analyses have shown the ability of oilseeds and particularly linseed to improve the nutritional composition of milk fatty acids (Glasser et al, 2008;Leduc et al, 2017;Meignan et al, 2017).…”
Section: Milk Fatty Acid Compositionmentioning
confidence: 99%